The Role of Career Development in the Relationship between Project-based Organization and Human Resource Management: Evidence from Tunisia - Hedhili, Mohamed Ali; Boudabbous, Sami (International Review of Management and Marketing, 2021)
The globalization of markets, the intensity of competition, and the evolution of technology have led to the appearance of new organizational forms based on projects. Faced with these changes, companies are forced to review and rethink their human resources management system to better adapt to the project environment. Career development is an essential factor in human resource management. This study aimed to understand the role of career development in the relationship between project-based organization (PBO) and human resources management (HRM). To this end, we conducted a qualitative study based on 31 interviews among Tunisian project managers. The results show that interviewees often lack such career development opportunities because of the temporary nature of their jobs. Project managers have to be responsible and proactive in developing their career path by maintaining and developing their skills. Keywords: Career development, project-based organization, human resource management, skills, qualitative research, Tunisia. JEL Classifications: J24, M12 DOI: https://doi.org/10.32479/irmm.11416